D23. Recent Advances on Smoking Health Effects 2010
DOI: 10.1164/ajrccm-conference.2010.181.1_meetingabstracts.a5441
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of 10 Cigarette Smoke Condensates On Primary Human Airway Epithelial Cells By Comparative Gene And Cytokine Expression Studies

Abstract: Cigarettes vary in tobacco blend, filter ventilation, additives, and other physical and chemical properties, but little is known regarding potential differences in toxicity to a smoker's airway epithelia. We compared changes in gene expression and cytokine production in primary normal human bronchial epithelial cells following treatment for 18 h with cigarette smoke condensates (CSCs) prepared from five commercial and four research cigarettes, at doses of~4 mg/ml nicotine. Nine of the CSCs were produced under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Some studies have reported that histologically normal large airway epithelial cells of smokers display allelic loss [ 10 ] and p53 mutations [ 11 ]. An in vitro study by Pickett et al [ 12 ] found that when a single source of human airway epithelial cells was exposed to the same dose of cigarette smoke condensate from 10 different cigarettes, 21 genes were altered by 9 of the 10 cigarettes. In addition, based on the transcriptome profiling, Spira et al [ 13 ] have indicated that smoking induces the expression of genes involved in redox stress and xenobiotic metabolism in the large airway epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that histologically normal large airway epithelial cells of smokers display allelic loss [ 10 ] and p53 mutations [ 11 ]. An in vitro study by Pickett et al [ 12 ] found that when a single source of human airway epithelial cells was exposed to the same dose of cigarette smoke condensate from 10 different cigarettes, 21 genes were altered by 9 of the 10 cigarettes. In addition, based on the transcriptome profiling, Spira et al [ 13 ] have indicated that smoking induces the expression of genes involved in redox stress and xenobiotic metabolism in the large airway epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of particulate phase of CS for 2h/d for days altered oxidative homeostasis in the lungs in Sprague Dawley rats as a result NQO1/actin ratio as well as NQO1 enzyme activity were increased [128]. Similarly, exposures of primary normal human bronchial epithelial cells to cigarette smoke condensates for 18 h strongly increased NQO1 expression compared to non-treated control cells [129]. However, with chronic exposure to cigarette smoke there is evidence of decreased Nrf2 activation and subsequent decrease in Nrf2-target genes including HO-1 and NQO1 [130,131].…”
Section: Inhibitors Factors Affecting Of Nqo1 Expression or Activitymentioning
confidence: 97%
“…The increased expression of NQO1 has been shown in human bronchial epithelial cells after stimulation with cigarette smoke condensate from commercial and research cigarettes for 18 h earlier. 49 Interestingly, expression of HMOX1 was increased only in THP-1 cells (Fig. 2B).…”
Section: Discussionmentioning
confidence: 89%